Using Apache Jena Fuseki Server for Execution of SPARQL Queries in Job Search Ontology Using Semantic Technology (International Journal of Innovative Research in Computer Science & Technology, 2022)
The "SPARQL Protocols as well as RDF  Query Language" allows users to query information from  a database or any other data source that can be mapped to  RDF. The SPARQL standard, created and supported by the  W3C, allows developers and users to concentrate on  whatever they wants to know instead of how a database is  organized. The proposed paper presents a Job Search  Ontology to help the employers, by recommending the  most eligible candidates for a particular job in IT domain  and, on the other hand, to propose jobs to the aspiring  candidates, matching their profiles with the existing job  offers. This paper also discussed the continuous demand  for qualified candidates in the Information Technology  (IT) domain has empowered the use of e-Recruitment  tools, which are becoming more and more exploited at the  expense of the traditional methods in this paper. The major  purpose of this research is to create an ontologies using the  Protégé ontology construction tool, which is then used to  run Simple Protocols as well as RDF (Resource  Description Framework) Query Language (SPARQL)  queries on it. This proposed system utilized Apache Jena  Fuseki Server for execution of SPARQL queries for Job  Search Ontology and it is very useful in upcoming days.
Keywords: Apache Jena Fuseki; Job Search; Ontology; Semantic Web; SPARQL